Comparative population structure of two dominant species, Shinkaia crosnieri (Munidopsidae: Shinkaia) and Bathymodiolus platifrons (Mytilidae: Bathymodiolus), inhabiting both deep‐sea vent and cold seep inferred from mitochondrial multi‐genes. Issue 11 (23rd April 2016) - Shen, Yanjun; Kou, Qi; Chen, Weitao; He, Shunping; Yang, Mei; Li, Xinzheng; Gan, Xiaoni
Abstract: Deep‐sea hydrothermal vents and cold seeps, limited environments without sunlight, are two types of extreme habitat for marine organisms. The differences between vents and cold seeps may facilitate genetic isolation and produce population heterogeneity. However, information on such chemosynthetic fauna taxa is rare, especially regarding the population diversity of species inhabiting both vents and cold seeps. In this study, three mitochondrial DNA fragments (the cytochrome c oxidase submit I (COI), cytochrome b gene (Cytb), and 16S) were concatenated as a mitochondrial concatenated dataset (MCD) to examine the genetic diversity, population structure, and demographic history of Shinkaia crosnieri and Bathymodiolus platifrons . The genetic diversity differences between vent and seep populations were statistically significant for S. crosnieri but not for B. platifrons . S. crosnieri showed less gene flow and higher levels of genetic differentiation between the vent and seep populations than B. platifrons . In addition, the results suggest that all the B. platifrons populations, but only the S. crosnieri vent populations, passed through a recent expansion or bottleneck. Therefore, different population distribution patterns for the two dominant species were detected; a pattern of population differentiation for S. crosnieri and a homogeneity pattern for B. platifrons . These different population distribution patterns were related to both extrinsic restrictive factors and intrinsic factors. Based on the fact that the two species were collected in almost identical or adjacent sampling sites, we speculated that the primary factors underlying the differences in the population distribution patterns were intrinsic. The historical demographics, dispersal ability, and the tolerance level of environmental heterogeneity are most likely responsible for the different distribution patterns. Abstract : Intraspecific genetic exchanges have been found for Bathymodiolus mussels across thousands of kilometers between vent and seep sites, but not for Shinkaia crosnieri . Our results showed a pattern of population differentiation for Shinkaia crosnieri and a pattern of homogeneity for Bathymodiolus platifrons .